PENGARUH KOMPETENSI, KOMITMEN ORGANISASI SERTA BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA DAN KINERJA PEGAWAI PADA SEKRETARIAT DAERAH KABUPATEN KUTAI TIMUR - Kartini . (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
This study aims to determine how much influence the competence, organizational commitment and organizational culture on job satisfaction as well as the influence of competence, organizational commitment and organizational culture and job satisfaction to employee performance at the Secretariat of the East Kutai Regency. The results showed that the results of the first substructure equation indicates that Job Satisfaction in East Kutai Regency Secretariat influenced by competence, organizational commitment and organizational culture, in the first substructure competence and organizational commitment positively influence organizational culture while negatively impact on the Job Satisfaction the Secretariat of the East Kutai Regency.